Anthelmintic Test of Combination of Carrot Peels (Daucus carota L.) and Pineapple Peels (Ananas comusus) Juice Against Silkworms (Tubifex sp) - Yossy Febryarti; Yetti Hariningsih; Oktaviarika Dewi H (Duta Pharma Journal, 2022)
Background: Anthelmintics is a treatment used as an anti-worm that can eradicate worms in the human and animal bodies, one of which is against silk worms (Tubifex sp). One of the plants that may be used as anthelmintics is carrot skin (Daucus carota L.) and pineapple skin (Ananas comusus). Carrot peel contains flavonoids, quercetin, and tannins as anthelmintics and pineapple peel contains flavonoids, bromealin enzymes and tannins, so researchers are interested in making a combination of carrot peel juice and pineapple peel juice as an anthelmintic against silk worms (Tubifex sp). Objective: This study aims to determine the effectiveness of the combination of carrot peel and pineapple peel juice in eradicating silk worms (Tubifex sp). Methods: The method used is the squeeze method, specific specific standardization, lethal time test, paralysis time test. , the anthelmintic activity test of the combination of carrot peel juice and pineapple peel extract with concentrations of F1 25%: 75%, F2 50%: 50%, F3 75%: 25% using positive control Albendazole 0.06% w/v. The research data were analyzed using the Oneway Anova test. Results: The results of this study showed that the combination of carrot peel extract 75%: pineapple peel 25% had the best anthelmintic effectiveness against the lethal time. The anthelmintic effectiveness test obtained from the combination of carrot juice 25%: pineapple juice 75% showed the best results during paralysis time. The lethal time test of the combination of carrot peel and pineapple juice obtained an average time of death in F1 of 15.32 minutes. In F2, the average time of death was 18.155 minutes, while in F3 it was 20.37 minutes and the Oneway Anova result was p=0.000 (p<0.05). The paralysis time test for the combination of carrot peel and pineapple juice was found to have an average paralysis time of 13.625 minutes in F1. In F2, the average paralysis time was 13,733 minutes, while in F3 18,712 minutes and the Oneway Anova result was p=0,000 (p<0,05). Conclusion: The best combination of juice for the time of death is F1 with a concentration of 25% carrot juice: 75% pineapple juice, while the best combination for paralysis time is F1 with a 25% carrot juice concentration: 75% pineapple juice.                                                                          Keywords : Carrot Peels (Daucus carota L.), Pineapple Peels (Ananas comosus), Anthelmintics, Tubifex sp